2015
DOI: 10.3389/fpls.2015.01054
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Responses of Apple Tree Floral Phenology to Global Warming in Contrasting Climatic Regions

Abstract: The responses of flowering phenology to temperature increases in temperate fruit trees have rarely been investigated in contrasting climatic regions. This is an appropriate framework for highlighting varying responses to diverse warming contexts, which would potentially combine chill accumulation (CA) declines and heat accumulation (HA) increases. To examine this issue, a data set was constituted in apple tree from flowering dates collected for two phenological stages of three cultivars in seven climate-contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 49 publications
0
29
0
2
Order By: Relevance
“…). Premises of endodormancy break failure, that is lack of chilling delaying endodormancy break and subsequently budburst date, are actually already visible in long‐term phenological series of apple tree in Nîmes (Legave et al ., ). Endodormancy break failure has been shown to be responsible for local population extinction at species southern range margins in previous modeling studies (Morin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…). Premises of endodormancy break failure, that is lack of chilling delaying endodormancy break and subsequently budburst date, are actually already visible in long‐term phenological series of apple tree in Nîmes (Legave et al ., ). Endodormancy break failure has been shown to be responsible for local population extinction at species southern range margins in previous modeling studies (Morin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…proximity of neighboring plants) environments have a cumulative effect on tree morphology and architecture over consecutive growing seasons. It has been shown that besides their effect on budburst phenology (Legave et al ., ) mild winter temperatures compared to cold winter temperatures significantly decrease branching frequency on stems with similar size and shape (e.g. apple, Dutra Schmitz et al ., ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Such changes can have a devastating impact on the composition of several plant communities because changes in flowering time may, for instance, induce mismatches between plants and their respective pollinators and thereby compromise the reproduction and distribution of several species (Becklin et al, 2016;Polce et al, 2014;Springer & Ward, 2007). These results are even more worrying when we also consider the increase in global average temperature, another factor that has been directly associated with phenological changes in many species (Bock et al, 2014;Legave, Guédon, Malagi, Yaacoubi, & Bonhomme, 2015;Mulder, Iles, & Rockwell, 2017). Thus, it is clear that the effect of high [CO 2 ] on the performance, survival, and distribution of species worldwide represents one of the greatest uncertainties related to climate change because its effects are extremely variable and also depend on a range of other factors.…”
Section: The Controver S Ial Role Of C Arbon D I Oxide: a P Otentiamentioning
confidence: 99%